2002
DOI: 10.1002/ajim.10030
|View full text |Cite
|
Sign up to set email alerts
|

Neurobehavioral disturbances arising from occupational toluene exposure

Abstract: In this study, low present exposure levels to toluene were associated with decrements of memory test performances.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0
6

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(41 citation statements)
references
References 28 publications
3
32
0
6
Order By: Relevance
“…Chouareire and collaborators found deficits in workers exposed to toluene correlated with present exposure but not cumulative exposure to toluene (2). Longitudinal studies of solvent exposed workers who had not developed neurocognitive complaints reported subclinical deficits but, similar to the findings of Rosenberg et al, no dose-response relationships at the doses observed (3 -5).…”
Section: Lettersupporting
confidence: 61%
See 1 more Smart Citation
“…Chouareire and collaborators found deficits in workers exposed to toluene correlated with present exposure but not cumulative exposure to toluene (2). Longitudinal studies of solvent exposed workers who had not developed neurocognitive complaints reported subclinical deficits but, similar to the findings of Rosenberg et al, no dose-response relationships at the doses observed (3 -5).…”
Section: Lettersupporting
confidence: 61%
“…In these patients, cognitive disabilities wax and wane with exposures (1) and correlate with present but not cumulative exposures to solvents (2). Neuropsychiatric testing has been used to document abnormalities.…”
Section: Lettermentioning
confidence: 99%
“…The symptoms of the most exposed painters correlated well with the main symptoms of the CSE: fatigue, poor memory, difficulty in concentration, emotional lability and depression [Edling et al, 1990], where memory is suggested to be the first mental faculty to be impaired [Chouaniere et al, 2002], which is reflected in the EQ domain of memory and concentration [Carter et al, 2002]. In our study, the painters with most exposure in the 1960/70s and 1980s had the most symptoms.…”
Section: Discussionmentioning
confidence: 60%
“…Einerseits deuten Studienergebnisse darauf hin, dass erste Leistungsbeeinträchtigungen ab 96 mg/m³ auftreten können [64], aber andererseits konnten in groß angelegten Querschnittsstudien [63] keinerlei Effekte bis zu Konzentrationen von 350 mg/m³ nachgewiesen werden. Zudem zeigt eine Metaanalyse, dass relevante Effekte in diesem Expositionsbereich von 96 bis 350 mg/m³ für einzelne der angewandten Tests zu Gedächtnis und Reaktionszeit nicht zu erwarten sind [113].…”
Section: Verhaltenstoxizitätunclassified